Challenges in Teaching Integrated Intensive Course through Technology-Enhanced Language Learning with SAMR Model - Waode Ade Sarasmita Uke; Nurdin Noni; Muhammad Basri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examined the challenges of teaching an Integrated Intensive Course (IIC) using Technology-Enhanced Language Learning (TELL) with the SAMR model. The study utilized a qualitative case study method and employed purposive sampling to choose experienced lecturers in Technology-Enhanced Language Learning (TELL) deployment. Data was collected by observation, interviews with the lecturers, and field note. Thematic analysis was used to examine the gathered data. The study shows that challenges in teaching Integrated Intensive Course through Technology-Enhanced Language Learning included restricted availability of suitable devices, student passivity, large class sizes, insufficient training, inadequate teaching resources, and issues with heat and equipment in traditional classrooms. The findings reveal that the challenges in teaching IIC through TELL were limited access to adequate devices, lack of student initiative, large class size, lack of training, inadequate teaching materials, and heat and equipment problems in physical classrooms.